The Development of Newtonian Mechanics Conceptual Change Texts to Overcome Students’ Misconceptions - Syuhendri Syuhendri (Journal of Education and Learning (EduLearn), 2018)
The research aimed to develop a valid and practical Conceptual Change Texts (CCT) of Newtonian mechanics materials. The method used was educational research and development. The data were collected using questionnaires and expert validation sheets, as well as questionnaires and interviews with students. The design of the CCT was developed based on the conceptual change theory using the following format: situation, questions, space for answers and reasons, misconception forms, and correct concept explanations. There have been 21 developed units of the CCT distributed in four chapters, i.e. Basic Laws, Applications of the Basic Laws, Work and Energy, and Impulse and Momentum. The results of the data analysis revealed that the CCT had content, conformity with needs, language, presentation, and graphic feasibility levels of 70%, 40%, 80%, 90%, 87%, respectively to mean that the teaching materials were very valid. Based on the practicality test, the teaching materials were very practical, i.e. 87%. In other words, the Newtonian mechanics CCT was easy to read and understand and could be used to change misconceptions. Educators can use these supplement teaching materials in the Basic Physics courses in college and in mechanics topics in a high school.